Mercurial : the definitive guide - O'Sullivan, Bryan (O'Reilly Media, 2009)
This instructive book takes you step by step through ways to track, merge, and manage both open source and commercial software projects with Mercurial, using Windows, Mac OS X, Linux, Solaris, and other systems. Mercurial is the easiest system to learn when it comes to distributed revision control. And it's a very flexible tool that's ideal whether you're a lone programmer working on a small project, or part of a huge team dealing with thousands of files. Mercurial permits a countless variety of development and collaboration methods, and this book offers several concrete suggestions to get you started. This guide will help you: Learn the basics of working with a repository, changesets, and revisions Merge changes from separate repositories Set up Mercurial to work with files on a daily basis, including which ones to track Get examples and tools for setting up various workflow models Manage a project that's making progress on multiple fronts at once Find and fix mistakes by isolating problem sources Use hooks to perform actions automatically in response to repository events Customize the output of MercurialMercurial: The Definitive Guide maintains a strong focus on simplicity to help you learn Mercurial quickly and thoroughly.